Principals’ entrepreneurial leadership practices in school fund raising activities - Ghazali, Siti Sabihah (2020)
Insufficient school funding has become among the unresolved issues in the education administration. Therefore, entrepreneurial leadership emerges in the school administration to facilitate school transformation and the practices of entrepreneurs. However, further knowledge needs to be gained on the practices of entrepreneurial leadership for fundraising, the importance of entrepreneurial leadership in schools, the integration of stakeholders with the schools done by school principals, and the enculturation of entrepreneurial school culture. Accordingly, three research questions were designed to determine entrepreneurial leadership definition in school, the entrepreneurial leadership practices among principals in fundraising, and the school culture development by school principals through entrepreneurial leadership. Thornberry Entrepreneurial leadership (2006), Lunenburg Open System Model (2010), Cameron and Quinn’s (1999) Adhocracy Theory, and Knight’s Financial Management Model (1993) were implemented in the theoretical framework development. Two school principals who implemented entrepreneurial leadership and actively conducted fundraising activities in school led the schools of different backgrounds and locations. As a result, different cases were presented in this study. The collection of data through 18 semi-structured interviews was followed with observations and document analysis. The within-case and cross-case analyses were conducted through Atlas ti. software and Microsoft Tables. Two categories were obtained for entrepreneurial leadership definition in school. These categories were opening the schools to the external environment and raising funds for school development. Two themes were then found, providing answers regarding the entrepreneurial leadership practices in school fundraising, namely the integration of the Role of Parents and Teachers Association (PTA) with the school vision, and sharing knowledge. Meanwhile, teamwork planning and networking were found as the themes of the development of entrepreneurial school culture. Four major conclusions were formulated in this study. Firstly, besides the raise of school funds, entrepreneurship leadership is perceived as one of the mediums which contribute to the involvement of an external environment with the school. Secondly, school principals need to integrate the Parents Teachers Association (PTA) with school vision. Thirdly, the entrepreneurship knowledge possessed by principals should be shared, so that the principals could implement fundraising in school through entrepreneurial leadership. Fourthly, to encourage outside parties’ engagement with school parties, the school entrepreneurship culture development is based on teamwork planning and effective networks. Theoretically, four dimensions in Thornberry Entrepreneurial Leadership are associated with the school’s fundraising success and entrepreneurial culture development. It is recommended that entrepreneurial leadership is emphasized in the National Professional Qualification for Educational Leaders (NPQEL). With this emphasis, school principals would be able to improve their entrepreneurial leadership skills and enhance their qualities as entrepreneurs in school administration. Last but not least, the empowerment of PTA in schools is important as it is the first step towards successful fundraising and entrepreneurial culture development in school.